2018
DOI: 10.1016/j.virol.2018.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of Sichuan takin fecal sample viromes reveals novel enterovirus and astrovirus

Abstract: The Sichuan takin inhabits the bamboo forests in the Eastern Himalayas and is considered as a national treasure of China with the highest legal protection and conservation status considered as vulnerable according to The IUCN Red List of Threatened Species. In this study, fecal samples of 71 Sichuan takins were pooled and deep sequenced. Among the 103,553 viral sequences, 21,961 were assigned to mammalian viruses. De novo assembly revealed genomes of an enterovirus and an astrovirus and contigs of circoviruses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…The phylogenetic trees of the ORF2 genes of AstV SLO/D5-14 and AstV SLO/D12-14 strains and other AstV strains showed that the roe deer AstV strains were also related to other bovine AstVs, porcine AstV2 strains, yak AstV, porcupine AstV and dromedary AstVs forming a highly supported group of sequences distantly related to MAstV genogroups I and II, that might constitute a new MAstV genogroup, as proposed by Guan et al [34].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The phylogenetic trees of the ORF2 genes of AstV SLO/D5-14 and AstV SLO/D12-14 strains and other AstV strains showed that the roe deer AstV strains were also related to other bovine AstVs, porcine AstV2 strains, yak AstV, porcupine AstV and dromedary AstVs forming a highly supported group of sequences distantly related to MAstV genogroups I and II, that might constitute a new MAstV genogroup, as proposed by Guan et al [34].…”
Section: Discussionmentioning
confidence: 55%
“…According to the latter authors, the MAstV genus consists of at least 33 species, of which only 19 are currently officially recognized as genotype/species by the ICTV. The phylogenetic and aa pairwise distance analysis of ORF2 sequences revealed a cluster of closely related AstV sequences, namely the two bovine strains from Hong Kong (BAstV-B18 and BAstV-B76-2) described by Tse et al [28], the four bovine strains (BAstGX-G1, BAstGX-J22, BAstGX-J27, BAstGX-J8 and BAstGX-J7) and two water buffalo strains (BufAstGX-M552 and BufAstGX-M541) from China, described by Alfred et al [31], two bovine strains from China (BAstV-GX7 and BAstV-GX27), one bovine strain BoAstV/JPN/Kago-shima1-7/2014 from Japan described by Nagai et al [33], the Sichuan takin AstV strain [34], two deer strains (CcAstV-1/DNK/2010 and CcAstV-2/DNK/2010) described by Smits et al [16] and the two roe deer strains (SLO/D5-14 and SLO/D12-14) described in this study. The aa identities of AstV strains SLO/D5-14 and SLO/ D12-14 compared to those of other AstV sequences from the described cluster were greater than 75.4 and 74.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Based on phylogenetic position, most viruses identified in the caecal content are likely to be associated with the rabbit diet or other commensal microorganisms, such as fungi and protozoa (Figure 2). To our knowledge, equivalent viral meta-transcriptomics analyses on caecal content have not been reported, although an abundance of plant and microorganism-associated viruses is consistent with the faecal viromes of other herbivores (Guan et al, 2018; Woo et al, 2014; Zhang et al, 2017). Importantly, we identified diverse novel viruses in rabbits – Racaecavirus and Orycavirus - that cluster with other vertebrate-associated viruses (in the Caliciviridae and the Picornaviridae , respectively) suggesting that the most likely hosts are the rabbits from which they were sampled.…”
Section: Discussionmentioning
confidence: 77%
“…In recent years a wide variety of mammalian domestic animal species were found positive for astroviruses in their feces; e.g. cattle (Woode & Bridger 1978), sheep (Snodgrass & Gray 1977), red deer (Tzipori et al 1981), takins (Guan et al 2018) and also domestic carnivores (Hoshino et al 1981;Williams 1980), mice (Kjeldsberg & Hem 1985) and pigs (Bridger 1980), but their role in the context of disease remained largely unclear.…”
Section: Introductionmentioning
confidence: 99%